Tranexamic acid in non-elective primary total hip arthroplasty. Issue 6 (June 2021) - Shichman, Ittai; Shaked, Or; Ashkenazi, Itay; Schwarzkopf, Ran; Warschawski, Yaniv; Snir, Nimrod
Highlights: Blood loss during and following non-elective total hip arthroplasty can be substantial and may require allogeneic blood transfusions which carries significant risks and morbidity for patients. Data regarding TXA efficacy in reducing blood loss in trauma patients undergoing non-elective primary total hip arthroplasty (THA) is sparse, and its routine use is not well established. Use of TXA treatment in patients undergoing non-elective THA led to a significant reduction in postoperative blood loss and in the proportion of patients requiring allogeneic blood transfusions. TXA use significantly reduced 1-year mortality after non-elective primary with no adverse effects. Abstract: Purpose: Blood loss during and following elective total hip arthroplasty (THA) can be substantial and may require allogeneic blood transfusions which carries significant risks and morbidity for patients. Intraoperative use of tranexamic acid (TXA) has been proven to reduce the need for allogeneic blood transfusion in elective THA patients. Data regarding TXA efficacy in reducing blood loss in trauma patients undergoing non-elective primary THA is sparse, and its routine use is not well established. Methods: This is a retrospective analysis of a consecutive cohort of patients who underwent non-elective primary THA in a tertiary medical center between January 1st 2011- December 31st 2019. The cohort was divided into two groups; one received perioperative TXA treatment while the other did not. Blood loss, blood product administration, peri and postoperative complications, readmissions and 1-year mortality were compared between groups. Results: A total of 419 patients (146 males, 273 females) who underwent THA were included in this study. The "TXA" group consisted 315 patients compared to 104 patients in the "no TXA" group. TXA use reduced postoperative bleeding, as indicated by changes in hemoglobin levels before and after surgery (ΔHb= -2.75 gr/dL vs. ΔHb= -3.34 gr/dL,   p <0.001) and by administration of allogeneic blood transfusions (7.0% vs. 16.3%,   p  = 0.004). Conclusion: Similar to the known effect of TXA in elective THA patients, the use of TXA treatment in patients undergoing non-elective THA led to a significant reduction in postoperative blood loss and in the proportion of patients requiring allogeneic blood transfusions.